if x=3,then find the value of k; 3(kx+2)=6+5x
Answers
Answered by
1
The answer is in picture.
Attachments:
![](https://hi-static.z-dn.net/files/dbc/7cdb7bedcbbb7cdbaea98435ec2034eb.jpg)
Answered by
4
Hii There!!
In this question we have given that , x= 3
So, substitute the value of 'x' in the given equation :
3 ( kx + 2 ) = 6 + 5x
=> 3 ( k × 3 + 2 ) = 6 + 5 × 3
=> 3 ( 3k + 2 ) = 6 + 15
=> 3k + 2 = 21/3
=> 3k + 2 = 7
=> 3k = 7 - 2
=> 3k = 5
=> k = 5/3
¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶
Hope it helps ☺️
In this question we have given that , x= 3
So, substitute the value of 'x' in the given equation :
3 ( kx + 2 ) = 6 + 5x
=> 3 ( k × 3 + 2 ) = 6 + 5 × 3
=> 3 ( 3k + 2 ) = 6 + 15
=> 3k + 2 = 21/3
=> 3k + 2 = 7
=> 3k = 7 - 2
=> 3k = 5
=> k = 5/3
¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶¶
Hope it helps ☺️
Similar questions
Environmental Sciences,
8 months ago
Math,
8 months ago
Math,
1 year ago
Biology,
1 year ago
Math,
1 year ago
Computer Science,
1 year ago